The Influence of Self Efficacy and Workload on Work on Employee Performance - Asraf, Asraf; Erwanto, Erwanto; Malihah, Lola; Yakin, Ikram; Suryani, Ni Kadek (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Self Efficacy is a factor that has a positive and significant effect on Employee Performance. In contrast to Self Efficacy, the average previous research shows a negative and significant impact on Employee Performance. This research is a quantitative research with an explanatory approach. This study used primary data collected by observation and questionnaire methods. The questionnaire was distributed to 250 Indomaret employees throughout the islands in Indonesia including Lampung province as the representative of the island of Sumatra, Banjarmasin as the representative of the island of Kalimantan, Kendari as the representative of the island of Sulawesi, Jakarta as the representative island of Java, and Bali as the representative island from the eastern side of Indonesia. The data obtained were analyzed using PLS 3.0. The results showed that Self Efficacy and Workload had a positive and significant effect on Employee Performance. Keywords : Employee Peformance, Self Eficacy, Work Laod